Fracture Resistance and Patterns of Fracture in Maxillary Complete Dentures Reinforced with Glass and Aramid Fiber Mesh under Dynamic Fatigue Loading - An In Vitro Study - Ancita Caroline Dsouza; Brijesh Shetty; Suhas Rao K (RGUHS Journal of Dental Sciences)
Aim The aim of this study was to evaluate and compare the fracture resistance and patterns of fracture in unreinforced glass amp aramid fiber mesh reinforced maxillary complete dentures under dynamic fatigue loading.Methods Forty-eight dentures were divided into three groups of 16 each. Unreinforced Glass and Aramid fiber mesh-reinforced maxillary dentures were fabricated using heat polymerized polymethylmethacrylate. They were stored in artificial saliva for six months. Fatigue testing was performed using a chewing simulator with 100 N load for 240000 cycles corresponding to one year. Fracture resistance was evaluated using a Universal testing machine. Patterns of fracture were categorized as complete incomplete fracture anterior amp posterior fracture anterior fracture posterior fracture and central deformation only loaded area. Statistical analysis was conducted using descriptive statistics ANOVA and Post-hoc Tukeys test.Results Aramid fibre mesh reinforced maxillary denture demonstrated the highest mean fracture resistance of 1561.82plusmn198.49 N followed by glass fibre mesh reinforced and unreinforced maxillary dentures with 1436.75plusmn231.39 N amp 1046.76plusmn94.61 N respectively. Unreinforced group showed complete fracture occurring in the midline while the reinforced maxillary complete denture showed incomplete fracture.Conclusion Glass and aramid fiber mesh reinforcement significantly increased the fracture resistance of dentures. Although not statistically significant aramid-reinforced dentures exhibited the highest fracture resistance than glass fiber. All intact fractures were noted with reinforced dentures facilitating easy repair. These findings may improve the longevity and durability of dentures.